Examining the Role of Innovative Leadership in Enhancing Student Achievement: Strategies and Outcomes - ALKENDI, MARWA (2024)
This research study examines the influence of innovative leadership tactics on student performance, emphasizing approaches and outcomes within various educational settings. As educational environments become increasingly complex, school administrators need to address the issue of reconciling established traditional approaches with the necessity for innovative practices that improve learning outcomes. This study seeks to examine how innovative leadership strategies might foster a culture of continuing development, cooperation, and adaptation among educators, thereby augmenting student success. The study used a mixed-methods approach, integrating qualitative data from semi-structured interviews with school administrators, while quantitative data collected by questionnaire administered to teachers. Key themes that emerged highlight the significance of a growth-oriented educational atmosphere, proficient communication, and the incorporation of real-world applications in learning activities. Administrators emphasized the important role of mentoring, professional development, and explicit goal setting in fostering effective teaching methods. Nonetheless, they also acknowledged considerable challenges, including reluctance to change, constrained resources, and time limitations. Research findings indicate that innovative leadership tactics enhance student engagement, critical thinking, and cooperation, however their effect on standardized academic outcomes is more complex. The study advocates for a more systematic approach to leadership that include focused professional development, improved communication, and assistance for gradual transformation. Moreover, cultivating a conducive atmosphere that promotes risk-taking and cooperation is vital. The study enhances the current research by offering insights into effective leadership tactics amid changing educational requirements. It provides practical suggestions for educational leaders aiming to implement innovation sustainably in accordance with educational objectives.